Visual studio code end-to-end editing and debugging tools for web developers - Johnson, Bruce (Indianapolis, Indiana Wiley, 2019)
Expert guidance on using Visual Studio Code for editing and debugging your web development projects Visual Studio Code, a free, open source, cross-compatible source code editor, is one of the most popular choices for web developers. It is fast, lightweight, customizable, and contains built-in support for JavaScript, Typescript, and Node.js extensions for other languages, including C++, Python, and PHP. Features such as debugging capability, embedded Git control, syntax highlighting, code snippets, and IntelliSense intelligent code completion support—several of which set it apart from the competition—help make Visual Studio Code an impressive, out-of-the-box solution. Visual Studio Code: End-to-End Editing and Debugging Tools for Web Developers helps readers to become familiar with and productive in Visual Studio Code. This up-to-date guide covers all of the essential components of the software, including the editing features of the workspace, advanced functionality such as code refactoring and key binding, and integration with Grunt, Gulp, NPM, and other external tools. New users, experienced developers, and those considering moving from another developer tool will benefit from this book’s detailed, yet easy-to-follow information on Visual Studio Code. This book: Teaches readers how to use Visual Studio Code to do full-stack development Explains the steps to install Visual Studio Code on Windows, Mac and Linux platforms Provides a foundation for non-users considering moving to Visual Studio Code Helps current users expand their knowledge of the tool and its available extensions Describes how to open a .NET Core project and get end-to-end execution and debugging functionality Visual Studio Code: End-to-End Editing and Debugging Tools for Web Developers is an invaluable guide for both professional and hobbyist web developers seeking immediately-useful information on Visual Studio Code.
Description based on print version record.
Keywords: Web applications